The Making of Juana of Austria : Gender, Art, and Patronage in Early Modern Iberia - García Perez, Noelia (Book collections on Project MUSE., 2021)
This volume is the result of the conference "Art, Power, and Gender: Juana of Austria and the Patronage of Art of in Renaissance Europe" held in the Department of Art History at the Universidad de Murcia in 2018.